1996
DOI: 10.1117/12.254208
|View full text |Cite
|
Sign up to set email alerts
|

Infrared polarization ship images and contrast in the MAPTIP experiment

Abstract: Shore-based polarized infrared images ofship target and background were obtained in the MAPTIP measurement series, using vertical and horizontal polarization filters. These images have been analyzed to yield degree ofpolarization and polarization contrast enhancement for targets with sea and sky background. Strong vertical polarization is observed in the sea surface emission near the Brewster Angle in the 8-12 micrometer (LWIR) band, whereas horizontal polarization due to reflection is usually dominant in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…Conversely, at larger wavenumbers the amount of scattered sunlight during the day is strong enough to increase the reflected-background atmosphere component sufficiently that it dominates the water-emitted radiance, resulting in a net positive (horizontal) polarization state. This kind of polarization signature has been measured (Cooper et al 1996), but the exact amount of positive polarization in the shortwave infrared spectral region depends strongly on atmospheric particulate scattering (Shaw 1999).…”
Section: Infrared Sea Surface Polarizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, at larger wavenumbers the amount of scattered sunlight during the day is strong enough to increase the reflected-background atmosphere component sufficiently that it dominates the water-emitted radiance, resulting in a net positive (horizontal) polarization state. This kind of polarization signature has been measured (Cooper et al 1996), but the exact amount of positive polarization in the shortwave infrared spectral region depends strongly on atmospheric particulate scattering (Shaw 1999).…”
Section: Infrared Sea Surface Polarizationmentioning
confidence: 99%
“…The impact of partially polarized radiance on radiometric measurements depends primarily on how the polarization alters the overall radiance and how the radiometer response varies with polarization. In fact, this relatively small instrument polarization sensitivity coupled with a similarly small amount of sea surface polarization does not present as big a problem in an application such as sea surface temperature (SST) radiometry as it does in a surveillance application where the polarization signature of a target is being measured (e.g., Egan 2000;Fetrow et al 2000;Howe et al 2000;Zeisse et al 1999;Cooper et al 1996). For these direct polarimetry problems, ignoring the instrument polarization sensitivity would result in an error that easily could be as large as the measured polarization value.…”
Section: Effect Of Polarization Sensitivity On Sea Surface Radiometrymentioning
confidence: 99%
See 1 more Smart Citation
“…), it has been suggested that by examining the polarization state of the IR image forming radiation, one can significantly improve the ability to see objects that are obscured by background clutter (4,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…To improve image contrast between ships and the ocean background, Cooper et al 10,11,13 and Walker et al 12 measured polarized images in the 3-5-and 8 -12-m wavelength bands, finding predominantly p polarization for the sea surface ͑Շ10% at 8 -12 m, less at 3-5 m͒. Sun glitter reduced the amount of p polarization and, especially in the short-wave band, often produced s polarization.…”
Section: Introductionmentioning
confidence: 99%